Theoretical and NMR-based Conformational Analysis of Phosphodiester-linked Disaccharides - Alexey G. Gerbst (Nature Portfolio, 2017)
Abstract The conformational behaviour of three phosphate-bridged dimannosides was studied by means of NMR and computational molecular modelling. First, the conformations of the phosphodiester linker were determined by quantum chemistry methods using dimethyl phosphate as a model. Then, a series of conformations was constructed for each of the studied molecules. Preliminary molecular dynamics (MD) simulations revealed that the inclusion of a cation had a drastic influence on the obtained results. Additionally, triethylammonium had the same effect as sodium as the counter-ion. After that, another series of MD simulations was run. The resulting MD trajectories were used to define the conformations responsible for the observed nuclear Overhauser effects and inter-nuclear coupling.